Effect of powder composition upon plasma spray-physical vapor deposition of 8YSZ columnar coating. Issue 10 (July 2020) - Yin, Jianan; Zhang, Xiao; Feng, Junli; Zhang, Xiaofeng; Song, Jinbing; Liu, Min; Zeng, Dechang; Mao, Jie; Deng, Chunming; Deng, Changguang; Deng, Ziqian; Zhao, Ruimin; et al.
Abstract: Agglomerated 8YSZ nano-powders for thermal barrier coating (TBC) were prepared by spray drying method. The morphology and diameter of 8YSZ powders were adjusted through controlling the solid content of the suspensions. Using prepared agglomerated 8YSZ nano-powders, columnar-structured coatings were obtained on Ni-based superalloy substrates by plasma spray-physical vapor deposition (PS-PVD). The experimental results proved that the spray dried powders characteristics were related to the solid content of suspensions. During the PS-PVD process, the deposition efficiency of the powders was improved with the increase of powder diameter due to the existence of thermophoresis. Moreover, it can be concluded by mathematical derivations that the top area of the plasma flame was sufficient for powder evaporation.